'Edible seaweeds' as an alternative to animal-based proteins in the UK: Identifying product beliefs and consumer traits as drivers of consumer acceptability for macroalgae. (September 2022) - Embling, Rochelle; Neilson, Louise; Randall, Tennessee; Mellor, Chloe; Lee, Michelle D.; Wilkinson, Laura L.
Highlights: UK consumers were accepting of hypothetical seaweed-based food products. Taste/ edibility was a strong driver of acceptance for seaweed-based foods. Food neophobia was identified as a barrier to acceptance for seaweed-based foods. Other product attributes (e.g., cost) were relatively poor predictors of acceptance. Taste/ edibility and familiarity partially mediated the negative effect of food neophobia on consumer acceptance. Abstract: Edible macroalgae (i.e., 'seaweeds') are a nutritious and sustainable alternative to animal-based proteins. However, consumption of seaweeds in Western countries remains low, and little is known about individual drivers of acceptance. The aim of this study was to further explore the consumer acceptability of seaweed-based food products in the UK. In an online study (N = 476), participants were presented with a general description of edible seaweeds, and descriptions of seaweed-based food products (e.g., 'seaweed burger'). Participants were asked to rate beliefs about product attributes, and reported acceptance in terms of liking, willingness to try, willingness to buy, and readiness to adopt as a meat alternative. It was predicted that positive beliefs about seaweed-based products would be significantly associated with greater acceptance, and that seaweed-based products would be more favourable than a general description of seaweeds. Supporting study hypotheses, structural equation modelling showed that positive beliefs about taste/ edibility and familiarity significantly predicted acceptance (p <.01). Taste/ edibility was higher for seaweed-based products compared to a general description of seaweeds (p <.001), and perceiving foods to be tasty and familiar mediated the negative effect of food neophobia on consumer acceptance (p <.05). Other product beliefs – including cost, healthiness, and sustainability – were relatively poor predictors of acceptance (p >.05). These results support the consumer acceptance of seaweeds, and identify scope for utilising specific attributes of seaweeds (as drivers of acceptance) in future product development.